An Approach to Quantify the Float Effect of Float Serves in Indoor and Beach Volleyball - Reiser, Mathias; Zentgraf, Karen; Kindermann, Stefan; Künzell, Stefan (Frontiers in Sports and Active Living, 2020)
The float serve is an effective weapon to impede the attack of the opposing team. Because of its great importance in indoor and beach volleyball, we measured and quantified the float effect. We recorded 24 float serves of 12 top athletes in beach volleyball and indoor volleyball, respectively and analyzed them using video analysis. We determined the 3D trajectories of the ball flight and developed two measures to describe the size of the float effect, the mean residuals and the anticipation error. Both were derived from regression models. These measures suggest that the float effect is greater in the vertical plane than in the horizontal plane, both for indoor and beach volleyball. Analyses of ball release velocities suggest that a certain ball release velocity is a necessary but not sufficient condition for ball floating. A validation of the float measurements with subjective expert ratings showed a correlation with the horizontal deviations. This study provides a new approach to analyze floating in on-court volleyball serves and broadens the knowledge for float effects in sports.